Distal extrahepatic cholangiocarcinoma mimicking groove pancreatitis: A case report and literature review - Han, Chaoqun; Ling, Xin; Sheng, Liping; Yang, Ming; Lin, Rong; Ding, Zhen (Frontiers in Oncology, 2022)
Background The differential diagnosis between cholangiocarcinoma and groove pancreatitis is quite challenging. Groove pancreatitis is commonly misdiagnosed as periampullary tumors. We reported a case of distal extrahepatic cholangiocarcinoma mimicking groove pancreatitis. Case report A 57-year-old male patient was transferred to our hospital after endoscopic retrograde cholangiopancreatography (ERCP) with stent placement in the common bile duct due to obstructive jaundice at a local hospital. Groove pancreatitis was considered based on the clinical manifestations and multiple examinations [including computed tomography (CT), magnetic resonance cholangiopancreatography (MRCP), and endoscopic ultrasonography (EUS)]. The patient’s symptoms and laboratory results almost returned to normal after conservative treatments. Interestingly, his symptoms and laboratory results worsened after the stent was removed. We performed a second EUS process and found a lesion in the lower common bile duct. Finally, the patient underwent pancreatoduodenectomy, and the diagnosis was confirmed as moderately differentiated adenocarcinoma of the common bile duct. Conclusion Our case highlights the fact that distal extrahepatic cholangiocarcinoma, which is a malignant disease, can mimic a benign condition like groove pancreatitis. Our case also raises the concern that performing stent placement through ERCP to relieve jaundice without a clear diagnosis could interfere with further evaluation of the disease.